Effect of rotor dynamics on steady state subsynchronous oscillations in series compensated power systems - Khan A.M.; Chauhan D.S.; Rao G.K. (My University, 2025)
This paper investigates the steady state subsynchronous resonance experienced by the turbine generator mechanical system. The study is made on the IEEE Benchmark model. For computation of the mechanical system mode frequencies, the Holzer's method, which is much simpler than the rigorous analysis, usually done in these studies, is first time used for the analysis of steady state subsynchronous resonance. © 1991 by Hemisphere Publishing Corporation.